2020
DOI: 10.1186/s13287-020-01802-8
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic role of convalescent plasma and mesenchymal stem cells in the treatment of severely ill COVID-19 patients: a clinical case report

Abstract: Acute respiratory distress syndrome virus-2 (SARS-CoV-2) responsible for coronavirus disease 2019 (COVID-19) infection, which causes global public health emergencies, has sped widely for more than 5 months and has the risk of long-term transmission. No effective treatment has been discovered to date. In the cases we report, the patient continued to deteriorate even after administration of antiviral drugs such as lopinavir/ritonavir, interferon-α, and ribavirin, as well as intravenous injection of meropenem, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…Following removing duplicates and screening of titles and abstracts, we evaluated 153 articles in full text. Among these, we found 45 relevant articles (4RCTs, 11 controlled NRSIs, 7 non-controlled NRSIs and 23 case reports) [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] . Extracted details are presented in Table 1 (RCTs, controlled NRSIs, and non-controlled NRSIs) and table 2 (case report(series)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following removing duplicates and screening of titles and abstracts, we evaluated 153 articles in full text. Among these, we found 45 relevant articles (4RCTs, 11 controlled NRSIs, 7 non-controlled NRSIs and 23 case reports) [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] . Extracted details are presented in Table 1 (RCTs, controlled NRSIs, and non-controlled NRSIs) and table 2 (case report(series)).…”
Section: Resultsmentioning
confidence: 99%
“… Clinical recovery and discharge from hospital. No adverse reactions Abdullah HM et al [51] Iraq Case series(n = 2) 46y/M; 56y/M 200 ml case1:10 days; case2: not reported Severe illness Clinical recovery and discharge from hospital No AEs Peng H et al [52] China Case report 66y/F 200 ml,twice Greater than 1:160. 10 days Severe illness On the fourth day after CPT, the absolute lymphocyte count returned to normal.…”
Section: Resultsmentioning
confidence: 99%
“… This was the first coronavirus case treated with umbilical cord cells reported from China. Liang et al,2020 [ 45 ] Case report Completed COVID-19 65-year-old woman hUCMSCs administrated intravenously for three times with antibiotics and thymosin α1 NA Reduced serum levels of bilirubin, CRP, ALT/AST along with improvement of vital signs. Decreased counts of white blood cells, and neutrophils and increase in lymphocyte count and throat swabs tests reported negative Peng et al, 2020 [ 46 ] Case report Completed COVID-19 66-year old female Convalescent plasma along with UC-MSCs Absolute lymphocyte count was improved after twice administration of convalescent plasma and no infusion or allergic reactions were seen after UC-MSC administration.…”
Section: Resultsmentioning
confidence: 99%
“…MSC-based therapy protocols to treat COVID-19 have been directed mainly to patients with moderate and severe clinical presentations [9][10][11][12][13][14][15][16][17][18]. Few numbers of studies included critically ill patients with COVID-19 under invasive mechanical ventilation [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stromal cells (MSCs) have been evaluated in compassionate use or clinical trials to treat COVID-19 pneumonia [9][10][11][12][13][14][15][16][17][18]. The rationale is to direct the immunomodulatory properties of MSCs to control the hyperin ammatory state and improve respiratory function.…”
mentioning
confidence: 99%